A New Day: Prime Time to Advance Afghan Clinical Education. (January 2016) - Rosenbaum, Stephen A.
In a previous issue of the journal, Richard Grimes discussed the role that legal clinics can play in facilitating access to justice in a post-conflict society, such as Afghanistan's, wracked by decades of civil war, external military intervention and consequential regime changes. 3 As foreign military forces withdraw, this Central Asian nation faces renewed security concerns and uncertainty about its politico-economic future. Yet, there is now a critical mass of law and Shari'a professors trained in the principles of experiential education, a few legal clinics are in place and many deans are keen on hosting a clinic, with a vigorous nod of approval from the higher education ministry. Piloting a clinical programme requires a team of faculty members who remain in continuous contact with their peers across the nation and across the globe. This should include a partnership with a reputable law school abroad; support from in-country administrative staff; and periodic visits by consultants. In addition, legal faculties and university administrators need to nurture clinical education by facilitating the development of new curricula, service learning and interdisciplinary and inter-university collaboration and exchange. While they needn't reinvent policies, protocols or perhaps even priority assessments, they must remain vigilant that clinical legal education not be divorced from the rest of the curriculum. The temptation to purchase durable goods will be great, but the clinic staff should be much more strategic and frugal about ways for students, staff and clients to access information and a space for consultation, training and work. Finally, an essential but elusive goal is to maintain a relationship with donors that is marked by candour and coordination of activities with other funders.